The effects of word exposure frequency on incidental learning of the depth of vocabulary knowledge - Teng, Feng (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examined the rate at which depth of vocabulary knowledge was learned and retained from reading a 300-headword graded reader, The Star Zoo. A total of 30 tertiarylevel students who learn English as a foreign language (EFL) in China volunteered to take part in a reading program. Incidental learning and retention of the depth of vocabulary knowledge was measured, complementing previous research along this line. The depth of vocabulary knowledge was examined by using 36 test items within six bands of frequency (more than 20 times to only once). The target words were substituted with pseudo-words. Two tests were employed to measure receptive and productive vocabulary knowledge. This study was completed in three sessions: Students read the book for the first time and finished tests; students read the book for the second time seven days later, and finished tests; finally, retention tests were completed three months later. The findings showed that incidental vocabulary learning through reading was very limited, and this learning was largely based on a high frequency of word occurrence, that is, the higher the frequency level was, the better the learners’ word-learning was. The number of times that Chinese EFL learners needed to encounter a word to recognize vocabulary knowledge was 14 times, and at least 18 times were needed for productive vocabulary knowledge. This study shows that attention to building knowledge of known words instead of solely introducing new words should be paid, and that both word exposure frequency and elaborate word processing are important as part of successful vocabulary development.